When America first met China : an exotic history of tea, drugs, and money in the Age of Sail - Dolin, Eric Jay (Liveright Pub. Corp., 2012)
Ancient China collides with newfangled America in this epic tale of opium smugglers, sea pirates, and dueling clipper ships.